(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The most important of Ibn Sina’s medical works is "The Canons of Medicine", which consists of five independent books. The second and fifth books contain information on pharmacology. In particular, the second book contains a tariff for more than 700 medicines, indicating the methods of their preparation and use. The fifth book describes 275 complex medicines.